MODEL TATAKELOLA PARIWISATA BERBASIS KOLABORATIF DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN - Wahyudin, Cecep; Firliandoko, Robby; Amalia, Nadia; Alfin Zulfa, Agra (Jurnal Governansi, 2024)
Tourism has great potential to improve the economy, create jobs, and support the development of various regions. However, improper tourism management can cause problems such as environmental degradation, excessive tourism and unequal economic benefits. Therefore, it is essential that collaborative-based tourism management can be effective in developing sustainable tourism. This research aims to identify collaborative-based tourism governance research in tourism development. The output of this research is to provide recommendations for a collaborative-based tourism governance model to impact tourism development in the Tenjolaya sub-district, Bogor Regency. The research method used was descriptive qualitative with 28 informants from the sub-district government and the Tenjolaya tourism awareness group. After the data was collected using data collection techniques through observation, interviews, field notes, analytical memos, and document elicitation, the researcher continued the analysis of the data obtained and then confirmed it using data validity techniques. The research results show that tourism governance in Tenjolaya has implemented collaborative governance even though it is still local, so every indicator still needs to be optimally fulfilled using the good tourism governance model and the public-private partnership model. Thus, tourism governance in Tenjolaya must focus on good tourism collaboration so that tourism goals in Tenjolaya can be achieved based on fulfilling indicators that support good tourism governance, good tourism development and good tourism sustainability.